Phenotypic Variation in Fruit Morphology among Provenances of Sclerocarya birrea (A. Rich.) Hochst. - Idah Mkwezalamba; Chimuleke R. Y. Munthali; Edward Missanjo (International Journal of Forestry Research)
Sclerocarya birrea (A. Rich.) Hochst. is a multipurpose fruit tree which is very useful in providing food security and meeting nutritional and economic needs. This study was conducted to assess eighteen provenances of Sclerocarya birrea planted in Mangochi, Malawi. The trial was assessed for fruit traits at fifteen years of age. There were significant (P<0.001) variations among the provenances in number of fruits, fruit weight, pulp weight, seed weight, fruit length, and diameter. Magunde provenance from Mozambique had the highest mean number of fruits, 2196 ± 200. Mangochi and Moamba provenances from Malawi and Mozambique were the most outstanding in the other parameters measured attaining the mean fruit weight of 20.89 ± 0.25 g and 25.67 ± 0.67 g, pulp weight of 25.70 ± 0.08 g and 21.55 ± 0.83 g, seed weight of 4.81 ± 0.35 g and 4.12 ± 0.18 g, fruit length of 2.61 ± 0.14 cm and 2.33 ± 0.07 cm, and fruit diameter of 2.33 ± 0.15 cm and 1.97 ± 0.08 cm, respectively. There was no significant (P>0.05) correlation between number of fruits and the other fruit traits. However, there were significant (P<0.05) and strong positive relationships between fruit weight and pulp weight (r=0.987) and fruit length and diameter (r=0.775). This suggests that fruit weight can be used indirectly for selection of pulp. Further studies should investigate fruit taste quality of products from the fruits.